2016
DOI: 10.1007/s12072-016-9736-3
|View full text |Cite
|
Sign up to set email alerts
|

APASL consensus statements and recommendations for hepatitis C prevention, epidemiology, and laboratory testing

Abstract: The Asian Pacific Association for the Study of the Liver (APASL) convened an international working party on ''APASL consensus statements and recommendations for management of hepatitis C'' in March 2015 to revise the ''APASL consensus statements and management algorithms for hepatitis C virus infection'' (Hepatol Int 6:409-435, 2012). The working party consisted of expert hepatologists from the Asian-Pacific region gathered at the Istanbul Congress Center, Istanbul, Turkey on 13 March 2015. New data were pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 210 publications
(184 reference statements)
0
100
0
Order By: Relevance
“…A study in Asia showed that up to 50% of patients with HCV are deemed unsuitable for treatment with IFN. Additionally, IFN therapy in Asian countries is often limited to major treatment centers, with limited access to isolated areas due to the infrastructure needed to ensure safety and appropriate treatment 10. According to a study by Wedemeyer et al,11 given the nature of IFN-based treatment, treatment response rates have been reported as low as 5%, even in countries with diagnosis rates greater than 50% 10…”
Section: Comparison Of Guidelines and Daasmentioning
confidence: 99%
“…A study in Asia showed that up to 50% of patients with HCV are deemed unsuitable for treatment with IFN. Additionally, IFN therapy in Asian countries is often limited to major treatment centers, with limited access to isolated areas due to the infrastructure needed to ensure safety and appropriate treatment 10. According to a study by Wedemeyer et al,11 given the nature of IFN-based treatment, treatment response rates have been reported as low as 5%, even in countries with diagnosis rates greater than 50% 10…”
Section: Comparison Of Guidelines and Daasmentioning
confidence: 99%
“…Patients should also be educated about the crucial importance of adherence to drugs, and the necessity for close supervision and laboratory tests during and after antiviral treatment. (2)(3)(4)(5)(6) The following points should be covered in detail (2-6):…”
Section: Pre-treatment Evaluationmentioning
confidence: 99%
“…HCV is primarily transmitted through percutaneous exposure to blood and blood products, mother-to-infant, contaminated devices shared with drug uses and sexual transmission (2)(3)(4)(5). HCV is not spread by hugging, holding hands, sneezing, coughing, or sharing eating materials or drinking glasses.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis C is a global health problem, and though the pangenotypic activity of SOF/VEL provides a wide-ranging therapy, specific populations with variable host genetics may benefit from tailored treatment plans. The high frequency of the favorable IL28B genotype, a single-nucleotide polymorphism (SNP) near the interleukin-28B gene, may contribute to high spontaneous HCV clearance in Asian populations [36]. The IL-28B gene does not appear to significantly alter DAA treatment outcome; however, per The Asian Pacific Association for the Study of the Liver (APASL) guidelines, IL28B genotyping could be clinically useful in interferon-based therapy [36].…”
Section: Future Directionsmentioning
confidence: 99%
“…The high frequency of the favorable IL28B genotype, a single-nucleotide polymorphism (SNP) near the interleukin-28B gene, may contribute to high spontaneous HCV clearance in Asian populations [36]. The IL-28B gene does not appear to significantly alter DAA treatment outcome; however, per The Asian Pacific Association for the Study of the Liver (APASL) guidelines, IL28B genotyping could be clinically useful in interferon-based therapy [36]. The ASTRAL studies provided basic information about SVR obtained by race, and no information was specific for Asian patients.…”
Section: Future Directionsmentioning
confidence: 99%